Experimental Investigations of Acoustic Characteristics of Two Counter-Rotating Rotors. - Rydlewicz, Wojciech; Błaszczak, Jarosław R. (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The presented investigations are continuation of earlier researches performed in the Institute of Turbomachinery (Lodz University of Technology, Poland). The main aim of this paper is to investigate the acoustics properties of the chosen configuration of a flow set–up consisting of two coaxial counter–rotating rotors. Description and analysis of measurements are presented. As a consequence, conclusions about possibility of noise reduction of such a system are presented. According to the EU Directives, the main areas of application are multi–purpose helicopters with two coaxial counter–rotating rotors, drones and future passenger–aircrafts with next–generation aeroengines.
Keywords: aeroengine; counter–rotating rotors; fan; acoustics; noise reduction; redukcja hałasu; akustyka; przeciwbieżne wirniki; wentylator